Kekuatan Genggaman : Golok Ciomas Simbol Kehormatan dan Tradisi - Haryadi, Ekananda; Wardoyo, Bambang Tri; Riyanti, Menul Teguh; Murwonugroho, Wegig; Haura, Nazzalla Izzabelle; Azizan, Ahamad Tarmizi (Jurnal Riset Rumpun Seni, Desain dan Media, 2025)
The Ciomas Golok is one of Banten’s intangible cultural heritage items, carrying profound historical, philosophical, and social meaning. More than a traditional weapon, it represents identity, honor, and the spirit of resistance against colonial rule. This study explores the origins and genealogy of the Ciomas Golok, analyzes the philosophy of “grip strength” encompassing physical, mental, and spiritual dimensions, and explains its role as a symbol of honor within Banten society. The research also examines its transformation in the modern era and compares it with other traditional weapons in the Nusantara and abroad. A qualitative method with a cultural ethnographic framework was applied. The research took place in Ciomas District, Serang Regency, as well as in museums, traditional markets, and cultural festivals. Data collection involved participant observation, in-depth interviews with blacksmith masters, community leaders, cultural figures, and youth, supported by literature documentation. Data analysis employed semiotics and symbolic anthropology, with validity maintained through triangulation of sources, methods, and theories. Findings show that the Ciomas Golok dates back to the Banten Sultanate era, evolving from an agricultural tool and weapon of resistance into a cultural artifact and creative economic commodity. The philosophy of “grip strength” highlights holistic values the golok as a symbol of honor, responsibility, and solidarity. Its continuing presence underscores the urgency of preservation. The study concludes that safeguarding the Ciomas Golok requires collaboration among blacksmiths, local communities, government, and academics to ensure its ongoing relevance as both a cultural emblem and an expression of Indonesian national identity.